An eagle eye on dowry demand cruelty and dowry death - "Magoo, Ish Kumar" (Delhi, 2004)
In this book an attempt is being made to cover all the subjects concerning dowry and dowry related offences with reference to up-to-date recent case law on the relevant points pronounced by the Apex Court and various High Courts.
Keywords: Dowry death